Exact disclosure prevention in two-dimensional statistical tables - Carvalho, Filipa D. (2005)
We propose new formulations for the exact disclosure problem and develop Lagrangian schemes, that rely on shortest path problems, to generate near optimal solutions. Computational experience is reported for 550 tables with up to 40,000 cells. A proven optimal solution was obtained for 95% of the instances and a near optimal solution was computed for each remaining instance as well as an upper bound on the deviation from the optimum.